An Exploratory Study of Pharmacist Perceptions of Opioid Interventions for Acute Pain. (February 2021) - Webb, Katie; Cernasev, Alina; Li, Minghui Sam; Gatwood, Justin; Cochran, Gerald; Hohmeier, Kenneth C.
Background: As the last health care provider encountered before an opioid is dispensed, pharmacists have a vital role in reducing unnecessary opioid exposure while facilitating access to non-opioid alternatives.Objective: To characterize pharmacist perceptions in providing interventions for patients with an opioid prescription for acute pain.Methods: This cross-sectional survey was administered over 3 months to pharmacy preceptors affiliated with the University of Tennessee Health Science Center College of Pharmacy. The electronic survey utilized 7 demographical and baseline questions, 1 open-ended question, and 5 Likert-type scales to assess the following domains: responsibility in making decisions, willingness to provide information, comfort in speaking to patients, willingness to use a standing order, and importance of following up with patients.Results: Of the 380 participants invited to participate, 126 responded to at least one question and 90 completed all survey questions. Most participants were PharmD graduates practicing in hospital and community settings. Participants felt that opioids are frequently overprescribed and pharmacist interventions are often necessary. Most participants reported that pharmacists and physicians share similar responsibilities in making opioid-related decisions. Participants were willing to provide information about opioid alternatives but were only somewhat comfortable speaking to patients. Responses to the open-ended question revealed the following themes: Significance of educating the patient; Importance of alternatives to opioid medications; Impacts of pharmacist interventions ; and Need for enhanced collaboration with physicians .Conclusions: Pharmacists face complex issues with limited clinical guidance when providing opioid-related interventions. Future research is needed to develop evidence-based clinical support tools and collaborative practice models.